Nephrotic Syndrome in a Child Suffering from Tetralogy of Fallot: A Rare Association - Pépé Mfutu Ekulu; Orly Kazadi-wa-Kazadi; Paul Kabuyi Lumbala; Michel Ntetani Aloni (Case Reports in Pediatrics)
Nephrotic syndrome is an uncommon complication of tetralogy of Fallot and has been rarely reported in pediatric population. We describe a 4-year-old female Congolese child who was referred for investigation for persistent dyspnea, edema, and cyanosis and nephrotic range proteinuria. Our patient presented with a tetralogy of Fallot and nephrotic syndrome. Conclusion. This case reminds us that children with tetralogy of Fallot may develop nephrotic proteinuria.